MENGEMBANGKAN POLITIK BERWATAK KERAKYATAN (STUDI ELABORASI NORMATIF-HISTORIS TERHADAP KONSEP UMMAH DALAM AL-QURAN) - Rohimin Rohimin (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
The Qur’an has a variety of concepts and offer of a problem, including in developing the political concept of Islam. This paper  attempts to collaborate and  offer the  effort to develop the  popular character of political Islam through  normative-historical approach. This approach is done  in order  to know  theoretically deductive and  its implementation in the  history of Islamic  civilization, especially  in matters relating  to politics in Islam. To develop the necessary political popular character main  instruments as development hubs.  Instrumentation Islamic politics in an attempt to strengthen the political as a force of human development, enhancement, and preservation of human dignity as well as advocacy for the rights and duties  of man.  Strength and honor  humanbeing can be realized  in a religious political system that is framed by a political instrument pluralist and humanist